Lived Experiences of General Education Teachers Handling Learners with Special Educational Needs in Inclusive Classrooms: A Basis for an Enhanced Inclusive Instruction Training Program - Tabigne, April (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study explored the lived experiences of general education teachers handling learners with special educational needs in inclusive classrooms as a basis for developing an Enhanced Inclusive Instruction Training Program. Anchored on the Universal Design for Learning framework, the study examined teachers’ instructional practices, classroom challenges, and adaptive responses in selected public and private schools in San Jose del Monte, Bulacan. A qualitative phenomenological research design was employed, using a researcher-developed semi-structured interview guide validated by experts. Twelve general education teachers were purposively selected based on their direct experience in teaching learners with autism spectrum disorder, attention-deficit/hyperactivity disorder, learning disabilities, and/or psychosocial disorders in inclusive classroom settings. Data were gathered through face-to-face or online interviews, supported by field notes, verbatim transcription, member checking, and thematic analysis with the aid of NVivo. Findings revealed that teachers used instructional differentiation, interest-based engagement, and peer-supported learning to address learner variability. However, they also experienced behavioral and participation difficulties, lack of formal training, workload and time constraints, limited institutional support, weak coordination, and assessment challenges. The study concluded that inclusive teaching relied largely on teacher initiative and experiential strategies, highlighting the need for structured, context-responsive professional development. The proposed training program focuses on inclusive education foundations, Universal Design for Learning, differentiated instruction, classroom management, flexible assessment, and collaboration. The study aligns with SDG 4, SDG 10, SDG 3, SDG 16, and SDG 17 by promoting inclusive education, reduced inequalities, well-being, institutional support, and collaborative partnerships. Its sustainability impact lies in strengthening educational, institutional, social, policy, and community support systems for inclusive classroom implementation.
Keywords: Differentiated Instruction; Enhanced Inclusive Instruction; General Education Teachers; Inclusive Classrooms; Inclusive Education; Teacher Resilience